Answer:
can you elaborate more on your question please
if this is the question or similar. An exponential function is given in the form f(x)-a*bx. If f(0)=3 and f(1)=15, what's the value of f(-2)?
this is how to solve it:
f(0) = 3 = a*b0 Therefore 3 = a (1)
f(0) = 3 = a*b0 Therefore 3 = a (1) f(1) = ab = 15
f(0) = 3 = a*b0 Therefore 3 = a (1) f(1) = ab = 15 3b =15
f(0) = 3 = a*b0 Therefore 3 = a (1) f(1) = ab = 15 3b =15 b =5
f(0) = 3 = a*b0 Therefore 3 = a (1) f(1) = ab = 15 3b =15 b =5 a =3 b =5
f(0) = 3 = a*b0 Therefore 3 = a (1) f(1) = ab = 15 3b =15 b =5 a =3 b =5 f(-2) = 3.5-2 = 3/25